Eliminating tyrosine sequence variants in CHO cell lines producing recombinant monoclonal antibodies. Issue 4 (15th February 2013) - Feeney, Lauren; Carvalhal, Veronica; Yu, X. Christopher; Chan, Betty; Michels, David A.; Wang, Yajun Jennifer; Shen, Amy; Ressl, Jan; Dusel, Brendon; Laird, Michael W.
Abstract Amino acid sequence variants are defined as unintended amino acid sequence changes that contribute to product variation with potential impact to product safety, immunogenicity, and efficacy. Therefore, it is important to understand the propensity for sequence variant (SV) formation during the production of recombinant proteins for therapeutic use. During the development of clinical therapeutic products, several monoclonal antibodies (mAbs) produced from Chinese Hamster Ovary (CHO) cells exhibited SVs at low levels (≤3%) in multiple locations throughout the mAbs. In these examples, the cell culture process depleted tyrosine, and the tyrosine residues in the recombinant mAbs were replaced with phenylalanine or histidine. In this work, it is demonstrated that tyrosine supplementation eliminated the tyrosine SVs, while early tyrosine starvation significantly increased the SV level in all mAbs tested. Additionally, it was determined that phenylalanine is the amino acid preferentially misincorporated in the absence of tyrosine over histidine, with no other amino acid misincorporated in the absence of tyrosine, phenylalanine, and histidine. The data support that the tyrosine SVs are due to mistranslation and not DNA mutation, most likely due to tRNATyr mischarging due to the structural similarities between tyrosine and phenylalanine. Biotechnol. Bioeng. 2013; 110: 1087–1097. © 2012 Wiley Periodicals, Inc.